Questions contractual regulation in the legal system regulation. (Journal of actual problems of jurisprudence, 2016)
This article discusses the theoretical issues of the contract , the legal nature of the contract , signs the contract.Agreement – is an agreement between two or more persons , aimed at the establishment, modification or termination of civil relations. Contracts is considered to be a kind of deals, and agreements on the rules of bilateral and multilateral transactions. Only bilateral or multilateral transaction in which there is mutual agreement of expression of two or more persons will contract.
Keywords: contract; agreement; will; freedom of contract